A comparison between anterolateral thigh perforator flap and abdominal pedicle flap in repair of hand injuries and tissue defects - Huang, Yinwei; Lu, Yefeng; Cao, Jinlin; Huang, Xuehui (Journal of the Pakistan Medical Association, 2023)
The purpose of this study was to compare the outcome of anterolateral thigh perforator flap and abdominal pedicled flap repair for treating traumatic tissue defects of the hand. A total of 140 patients with hand trauma tissue defects were randomly divided (random number table) into Group A and Group B, with 70 cases in each group. Group A was given anterolateral thigh perforator flap repair, while Group B was given abdominal pedicled flap repair. The healing time of wounds in Group A was noted to be shorter than that in Group B (P<0.001). At one week after surgery, VAS score, serum IL-6 and TNF-a levels in Group A were 4 times lower than those in Group B (p<0.001 for all). Anterolateral thigh perforator flap repair works more effectively on traumatic tissue defects of the hands than abdominal pedicled flap repair. ---Continue